Giuseppe Flavio a pezzi: per una ricostruzione di Chartres, Bibliothèque Municipale, 29 (70) - Pani, Laura (Scrineum, 2020)
This paper deals with the MS 29 (70) of the Bibliothèque Municipale of Chartres, a 10th century witness of Joseph Flavius’ Antiquitates Iudaicae and Bellum Iudaicum. The manuscript was severely damaged by the fire from 1944 and 211 fragments of it survive in different state of conservation, out of the 245 folios that once formed the codex. The research has allowed to reestablish the correct textual sequence of the fragments, all digitized in the Bibliothèque virtuelle des manuscrits mediévaux, describe the codicological and paleographical features of the manuscript, date it to the second half of the 10th century and make an hypotesis on its localisation between Fleury and Saint-Père of Chartres, two abbeys tightly connected from the second half of the 10th century inwards. The paper also gives some hints of the position of the manuscript in the textual transmission and investigates its relations with the MS 183 from the Burgerbibliothek of Bern.